Preliminary study of personality traits in Chinese lung cancer patients: Modification by neurotensin receptor 1 polymorphisms. (28th November 2016) - Ma, Hui; Cong, Zhengtu; Zhang, Hongyu; Tao, Jiangang; Yang, Chao; Song, Zhijie
Abstract: This study recruited 148 lung cancer patients and 157 healthy Chinese individuals to evaluate the personality traits of Chinese lung cancer patients using the Tridimensional Personality Questionnaire and to investigate the associations between these traits and the rs6090453C/G and rs6011914C/G polymorphisms of the neurotensin receptor 1 gene. The results demonstrated significant differences in the Tridimensional Personality Questionnaire total and subscale scores between the 2 groups. Significant differences were found in the reward dependence 2 (RD2) score between the rs6090453C/G genotypes and in the total harm avoidance (HA), HA1, HA2, HA4, and RD2 scores between the rs6011914C/G genotypes. Thus, patients with lung cancer have specific personality traits, and variations in the neurotensin receptor 1 gene may be involved in the biological mechanisms of the HA and RD personality traits.